Appropriate target range of INR and predictive factors of recurrent thrombosis and bleeding in patients with venous thromboembolism on warfarin - Peerasit Sae-Lim; Pirun Saelue (Scientific Reports)
Abstract Warfarin is the cornerstone of venous thromboembolism (VTE) treatment. An appropriate international normalized ratio (INR) range of prothrombin time can prevent recurrent VTE and decrease bleeding risk. This study aimed to identify the appropriate INR range for warfarin therapy and evaluate the predictive factors for recurrent VTE and bleeding events. This study included patients diagnosed with VTE and treated with warfarin. We compared three targets of the therapeutic INR range (1.5–2.5, 2.0–3.0, and 2.5–3.5). Among patients with VTE receiving warfarin, no significant differences in VTE recurrence were observed among the three INR targets. Patients with a target INR of 1.5–2.5 had lower bleeding rates than other groups. Smoking was a significant predictive factor for recurrent VTE. Transiently provoked VTE and active cancer were significant risk factors for bleeding, while the target range of INR 1.5–2.5 with good compliance was a protective factor for bleeding. In summary, a target INR of 1.5–2.5 effectively prevented recurrent VTE with minimal bleeding risk in patients taking warfarin. Smoking increases VTE recurrence risk, highlighting the importance of smoking cessation to reduce thrombotic risk. Shorter anticoagulant duration could balance thrombotic and bleeding risks in patients with transiently provoked VTE.